NEW FRONTIERS OF ANTARCTIC SUBGLACIAL LAKES EXPLORATION - Pavel Talalay; Alexey Markov; Mikhail Sysoev (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2013)
Antarctic subglacial aquatic environment have become of great interest to the science community because they may provide unique information about microbial evolution, the past climate of the Earth, and the formation of the Antarctic ice sheet. Nowadays it is generally recognized that a vast network of lakes, rivers, and streams exists thousands of meters beneath Antarctic Ice Sheets. Up to date only four boreholes accessed subglacial aquatic system but three of them were filled with high-toxic drilling fluid, and the subglacial water was contaminated. Two recent exploration programs proposed by UK and USA science communities anticipate direct access down to the lakes Ellsworth and Whillans, respectively, in the 2012/2013 Antarctic season. A team of British scientists and engineers engage in the first attempt to drill into Lake Ellsworth but failed. US research team has successfully drilled through 800 m of Antarctic ice to reach a subglacial lake Whillans and retrieve water and sediment samples. Both activities used hot-water drilling technology to access lakes. The main troublesome of the implemented and planned projects for accessing of Antarctic subglacial lakes is connected with the hydrostatic unbalance resulted in the upwelling of water into the hole with subsequent difficulties. The proposed RECoverable Autonomous Sonde “RECAS” would measure and sample subglacial water while subglacial lake is reliably isolated from surface environment, and at the same time the sonde is able to measure geochemical signals in situ throughout the depth of ice sheet on the way to the bed. All process is going on in semi-automatic mode, and the estimated duration of subglacial lake exploration at the depth of 3500 m is 8–9 months. The general concept of the sonde as well as proposed power-supply and performance are given.